Assessment of Knowledge, Awareness, and Practice Towards Radiation Protection among Physicians: A Cross-Sectional Study at Tobruk - Mardey A A Emayof; khlad Awath (Libyan Journal of Medical and Applied Sciences, 2025)
Physicians who request radiological imaging must have a broad background in determining the importance of diagnostic imaging requests for their patients, as well as an adequate understanding of the associated risks. Although the radiological doses are relatively low and the likelihood of delayed effects is minimal, it is vital to minimize exposures as low as reasonably achievable. Successfully achieving this objective requires a thorough understanding and unwavering commitment to following radiation protection procedures. This cross-sectional study aims to investigate physicians’ knowledge of radiation safety and their attitudes towards radiation protection. 121 non-radiologist physicians at Tobruk Town completed a survey between January and July 2023. Data was entered into Microsoft Excel and analyzed with SPSS, revealing several areas of inadequate knowledge. The proportion of physicians who had undergone a radiation protection course was less than 33%. A limited number of physicians demonstrated the ability to precisely respond to several scientific and knowledge-based questions. Only 18% of the participants demonstrated the ability to recognize the ALARA principle, and only 10% accurately ordered organs based on their radiation sensitivity. This study linked Libyan physicians’ inability to participate in the radiation safety training course to their insufficient level of knowledge. To bridge this knowledge gap, it is necessary to increase awareness of potential hazards and practice radiation protection against ionizing radiation through continuing medical education and training programs.